Asociación de úlcera gástrica y Helicobacter spp. en cerdos en Antioquia, Colombia - Rodriguez, Bernardo J.; Aranzazu, Diego; Ortiz, Laura C. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary The pigs develop frequently gastroesophagic ulcers (GU) and have been colonized by Helicobacter spp. As in the human has been communicated the association of these microorganisms with gastritis, gastric ulcer and gastric adenocarcinoma, the aim of this investigation was determine the association between the pig gastroesophagic ulcer (GU) and the colonization by Helicobacter spp. in Antioquia. We evaluated microscopically 30 stomachs that displayed GU and 30 without ulcer. Analysis of the results was made with a level of reliability of 95 % using the Chi square test. In this study, we show association between the natural infection with Helicobacter spp. and the UG disease, additionally we discuss about the zoonotic potential of these microorganisms in Antioquia.